Plantae vasculares in Lapponia orientali sponte nascentes. - Fellman, Nils Isak. (Helsingforsiæ : J. Simelii, 1864)
"E Notiser Sällskapet Fauna & Flora Fennica Förhaldingar, H. [1864. vii: 1-99 1869. viii: i-lxx]. Mode of access: Internet.